A predação por peixes em sinergia com o estado trófico determina a estrutura de tamanho da comunidade zooplanctônica em lagoas rasas de uma planície de inundação neotropical, Brasil. - Candeias, Donisete Aparecido das (2020)
The zooplankton body size is influenced by several factors, which in the natural ecosystem, can act directly, or interact, indirectly affecting the community structure. Water temperature, food availability, trophic status and predation by vertebrates are the main factors that influence the size structure of this community. Here we investigate how these factors can act on this characteristic of zooplankton directly or indirectly, mediated by the interaction between the factors. For this, we use a structural equation model that allows investigating complex interactions in natural ecosystems. The trophic state and the predation by fish were the main size planters of zooplankton. The trophic state positively influenced the small zooplankton, and indirectly the large zooplankton, mediated by the increase in fish abundance. The results indicated that the community size structure was regulated by top-down (predation) and bottom-up (nutrient availability) mechanisms, however the magnitude of the relationships was variable. Therefore, the results of the present study show that in tropical aquatic ecosystems there is a complex web of interactions that determine the structure of the zooplankton community.